2017
DOI: 10.1002/lno.10629
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen excretion by copepods and its effect on ammonia‐oxidizing communities from a coastal upwelling zone

Abstract: The role of zooplankton in microbial nitrogen turnover in marine environments is poorly understood. Here, we present results from two experiments designed to determine the excretion rate of ammonium and dissolved organic nitrogen (DON) by dominant copepods, Acartia tonsa and Paracalanus cf indicus, fed with two natural sized-fractioned diets (20-150 lm and < 20 lm), and its possible effects on the transcriptional activity of ammonia monooxygenase subunit A (amoA), a functional marker for ammonia-oxidizing arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…In the late-summer experiment, NH accumulation in the treatment with copepods fed with the 20-150-µm size-fraction diet suggested that nitrification processes occurred during the incubations. This was expected considering the previous findings of a tight coupling between excretion and ammonia oxidation (Molina et al, 2005(Molina et al, , 2012 and the functional microbial groups involved (Valdés et al, 2017). During the late summer experiment, the treatment with copepods fed with the <20-µm size-fraction diet was characterized by a high consumption of nitrogen compounds between the initial period and 4 h of incubation, with an NH In addition, the DOM quality, evaluated by changes in the DON:DOP ratio (Supplementary Figure 10), could influence the microbial response to copepod excretion product enrichments.…”
Section: Potential Fate Of Dissolved Organic and Inorganic Compounds supporting
confidence: 60%
“…In the late-summer experiment, NH accumulation in the treatment with copepods fed with the 20-150-µm size-fraction diet suggested that nitrification processes occurred during the incubations. This was expected considering the previous findings of a tight coupling between excretion and ammonia oxidation (Molina et al, 2005(Molina et al, , 2012 and the functional microbial groups involved (Valdés et al, 2017). During the late summer experiment, the treatment with copepods fed with the <20-µm size-fraction diet was characterized by a high consumption of nitrogen compounds between the initial period and 4 h of incubation, with an NH In addition, the DOM quality, evaluated by changes in the DON:DOP ratio (Supplementary Figure 10), could influence the microbial response to copepod excretion product enrichments.…”
Section: Potential Fate Of Dissolved Organic and Inorganic Compounds supporting
confidence: 60%
“…Among other organic C‐substrates, taurine stimulates growth in Nitrosocosmicus exaquare , thereby accelerating its ammonium‐oxidizing activity (Sauder et al 2017). Valdés et al (2018 b ) showed that ammonia oxidizing archaea are highly active in coastal waters off central Chile in winter in response to DON released by copepods, outcompeting ammonia‐oxidizing bacteria at ammonia concentrations close to the detection limit.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, although crustacean zooplankton are synthesizing taurine, the elevated taurine and DFAA release rates during the fall–winter period might also be attributed to taurine‐ and DFAA‐enriched diet and/or harmful phytoplankton. Additionally, the quality, quantity, composition, and the size of the available diet can strongly influence the release rates of DOM compounds by copepods (Frangoulis et al 2004; Valdés et al 2017) and thus, the organic C, N, and S available to heterotrophic prokaryotes (Valdés et al 2018 a , b ). The diversity of copepod species was higher in the fall–winter period, especially of small‐sized species, than in the spring–summer period (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…The nitrogen regime is mainly affected by human activities, including domestic sources, agricultural sources, livestock farming, and aquaculture sources. Except for the terrestrial sources, there are autogenous nitrogen sources, such as ammonium excretion by phytoplankton and zooplankton, and urea excretion by fish, which might affect the algal growth and species composition by the microbial loop (Arzul et al, 2001; Coello‐Camba et al, 2017; Glibert et al, 2016; Valdes et al, 2018). Generally, diatoms prefer nitrate as a source of nitrogen, with higher affinity coefficients than ammonium and urea in the culture experiment ( p < 0.05), whereas dinoflagellates prefer ammonium or urea (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%